Continuous Vagal Neuromonitoring Using the Laryngeal Adductor Reflex: Can Preincision Dyssynchrony Predict Intraoperative Nerve Behavior?. (12th March 2019) - Roldan, Maria De Los Angeles Sanchez; Téllez, Maria J.; Ulkatan, Sedat; Sinclair, Catherine F.
Abstract : Objective: The laryngeal adductor reflex (LAR) is an airway‐protective response triggered by sensory laryngeal receptors and resulting in bilateral vocal fold adduction. The normal morphology of the early R1 response resembles that of the compound muscle action potential (CMAP). However, in a small subset of patients, the morphology is dyssynchronous with multiple peaks. This study investigates whether preoperative LAR dyssynchrony predicts intraoperative nerve behavior during thyroid surgeries. Study Design: Retrospective case‐control study. Setting: US academic health center. Subjects and Methods: Opening and closing LAR waveforms from 200 patients with normal preoperative laryngeal examinations monitored continuously during thyroid surgeries using the LAR were analyzed. Area under the curve (AUC) and number of "events" during surgery (defined as any transient decline in AUC >50% baseline) were determined for patients who demonstrated opening dyssynchronous LAR traces compared to demographically matched controls. Results: Six patients had opening dyssynchronous LAR traces. These patients had significantly greater declines in R1 AUC than demographically matched patients with opening synchronized R1 traces ( P =. 007). Upon thyroid removal, 1 patient converted from a dyssynchronous to synchronous trace. Conclusions: Preincision dyssynchronous LAR waveforms may indicate subclinical, potentially reversible, neuropathy of the recurrent laryngeal nerve (RLN) and predict intraoperative RLN behavior. Preincision knowledge of R1 dyssynchrony can facilitate surgical planning as such patients may glean particular benefit from continuous intraoperative nerve monitoring, frequent tissue relaxation, and saline irrigation as means to minimize nerve stress intraoperatively.